Human Motor Cortex Functional Changes in Acute Stroke: Gender Effects - Di Lazzaro, Vincenzo; Pellegrino, Giovanni; Di Pino, Giovanni; Ranieri, Federico; Lotti, Fiorenza; Florio, Lucia; Capone, Fioravante (Frontiers in Neuroscience, 2016)
The acute phase of stroke is accompanied by functional changes in the activity and interplay of both hemispheres. In healthy subjects, gender is known to impact the functional brain organization. We investigated whether gender influences also acute stroke functional changes. In thirty-five ischemic stroke patients, we evaluated the excitability of the affected (AH) and unaffected hemisphere (UH) by measuring resting and active motor threshold and motor-evoked potential amplitude under baseline conditions and after intermittent theta burst stimulation (iTBS) of AH. We also computed an index of the excitability balance between the hemispheres, laterality indexes (LI), to evidence hemispheric asymmetry. Active motor threshold differed significantly between AH and UH only in the male group (p=0.004), not in females (p>0.200), and both LIAMT and LIRMT were significantly higher in males than in females (respectively p=0.033 and p=0.042). LTP-like activity induced by iTBS in AH was more frequent in females. Gender influences the functional excitability changes that take place after human stroke and the level of LTP that can be induced by repetitive stimulation. This knowledge is of high value in the attempt of individualizing to different genders any non-invasive stimulation strategy designed to foster stroke recovery.